Key infection and its applications in sensor networks - LIU Zhi-hong1; MA Jian-feng1; PANG Liao-jun1; PEI Qing-qi1 (Tongxin xuebao)
Key management has remained a challenging issue in sensor networks due to the constraints of sensor node resources.First,a probabilistic model to analyze the security of key infection was derived.Then a group based key infection to further improve its security performance was proposed.Finally,by combining the key infection with a lightweight key pre-distribution mechanism,a more secure key distribution scheme for sensor networks,Group based Key Infection with Key Pre-distribution,was presented.Analysis results show that proposed scheme presents a viable trade-off between security and resource consumption for smart dust sensor networks.